Somatic Symptoms in Depression; A Teaching Hospital Based Cross Sectional Study (Medical Forum Monthly, 2024)
Objective:The objective of the current study was to assess somatic symptoms in patients who were suffering from depression.Study Design: Cross sectional study.Place & duration of study: This study was conducted at the Department of Psychiatry & Behavioural Sciences, AIMTH affiliated to KMSMC Sialkot during October 2017.Material and methods: Adult consenting new patients of depression coming through OPD were included. Exclusion criteria were patients suffering from any other physical or psychiatric illness, minors or those refusing consent. In phase 1 clinical assessment was done according to ICD-10 criteria and Urdu version of Beck Depression Inventory- II (BDI- II) was administered. In the 2nd phase presenting complaints were noted. If the main presenting complaint was one or more somatic symptoms, they were recorded along with the demographic details on a sheet. The data was analyzed by SPSS v 21. Results: Majority of the patients of depression coming to our hospital were young married females from middle and lower income class with no or little education. 151 (63.71%) reported somatic symptoms. Headache was the most common 131 (22.05%) followed by muscle pain 86 (14.48%) and decreased appetite 85 (14.315%) generalized weakness 77 (12.96%) joint pains 71 (11.95%) gastrointestinal disturbances 59 (9.93%) tingling and burning sensations 38 (6.39%) and other symptoms by 47 (7.91%). Conclusion: Majority of the patients were young married females from middle and lower income class with no or little education. 151 (63.71%) reported somatic symptoms. Headache was the most common 131 (22.05%) followed by muscle pain 86 (14.48%) and decreased appetite 85 (14.315%).